Interleukin 21 controls tumour growth and tumour immunosurveillance in colitis-associated tumorigenesis in mice. Issue 12 (23rd September 2011) - Jauch, Dominik; Martin, Maria; Schiechl, Gabriela; Kesselring, Rebecca; Schlitt, Hans Jürgen; Geissler, Edward K; Fichtner-Feigl, Stefan
Abstract : Background and aims: Colitis-associated tumorigenesis is a balance between proliferation of tumour cells and tumour immunosurveillance. The role of T-helper-cell-derived cytokines in tumour growth is not fully understood. In this study the authors investigated the influence of interleukin (IL) 21 on intestinal tumorigenesis. Methods: Chronic colitis was induced in IL-21 −/− and littermate control wild-type mice with three cycles of 1.5% dextran sulphate sodium (DSS) over 7 days followed by 7 days of drinking water. Mice received an azoxymethane injection on day 0 of DSS-colitis to induce tumorigenesis. Immunohistochemistry was performed on inflamed and tumour-bearing areas of colons. Cytokine expression of isolated colonic CD4 T cells was determined by ELISA. Cytotoxic capacity of isolated colonic CD8 T cells targeting tumour cells was evaluated by flow cytometry and quantitative cytotoxicity assay. Apoptosis of tumour cells was determined by TUNEL assay of colonic sections. Results: Increasing expression of IL-21 was observed in chronic colitis, which showed functional importance, since IL-21 deficiency prevented chronic DSS-colitis development. Further, in the absence of IL-21, significantly fewer tumour nodules were detected, despite a similar extent of intestinal inflammation. In wild-type mice, 8.6±1.9 tumour nodules were found compared with 1.0±1.2 in IL-21-deficient mice. In tumour-bearing IL-21-deficient mice, intestinal inflammation was restored and partly dependent on interferon (IFN)-γ, whereas the inflammation in wild-type mice showed high IL-17A concentrations. In these rare tumours in IL-21-deficient mice, tumour cell proliferation (Ki-67) was decreased, while cell apoptosis was increased, compared with wild-type mice. Increased IFNγ expression in tumour-bearing IL-21-deficient mice led to increased tumour immunosurveillance mediated by cytotoxic CD8CD103 T cells targeting E-cadherin + colonic tumour cells and therefore limited tumour growth. Conclusion: These results indicate that IL-21 orchestrates colitis-associated tumorigenesis, leading to the hypothesis that high IFNγ and low IL-17A expression reduces tumour cell proliferation and increases tumour immunosurveillance.